Counting Caste: Censuses, Politics, and Castelessness in India. (December 2018) - Vithayathil, Trina
This article addresses the important question of how "upper"-caste power is reproduced in contemporary India, in the face of organized challenges from below. It argues that this process turns on the reproduction of castelessness . A long-standing site for the cultivation of castelessness has been the postcolonial census, which has limited the enumeration of caste to certain nonelites for the purposes of affirmative action reservations. However, in the aftermath of an intensive campaign to include a full castewise enumeration in Census 2011, the political leadership of the Indian National Congress Party conceded and reversed seventy years of census policy on caste. This article examines the institutional pushback within the executive bureaucracy in the year following the public concession to change census policy on caste. In doing so, it shows how bureaucratic actions and inactions reproduce both castelessness and upper-caste power in contemporary India.